Network flow optimization by Genetic Algorithm and load flow analysis by Newton Raphson method in power system - Razuan Hossain, Md; Kaiser, M. Shamim; Ali, Fahmid Iftekher; Monjurul Alam Rizvi, Md (2015 International Conference on Electrical Engineering and Information Communication Technology (ICEEICT), 2015)
The Optimal Power Flow (OPF) problem seeks to find the optimal operation of a electric power system that reduces a cost function of generation of active power that meets the total demand subject to some constraints. In this work, an attempt has been made to solve network flow optimization problem using Genetic Algorithm (GA) and load flow analysis by Newton Raphson method for a IEEE 9 bus system. The numerical analysis has been done in Matlab and results showed that the proposed approach has been used to find the optimal operating point of the power system network.